ANALISIS PERBANDINGAN METODE NUMERIK DALAM MENYELESAIKAN PERSAMAAN-PERSAMAAN SERENTAK - Fransiskus Gatot, Iman Santoso (Widya Warta, 2011)
One of the uses of numerical method is to determine the values of variables of equations simultaneously. The methods which can be used to determine the values of variables of simultaneous equations are Newton-Rapshon method and iteration method. Between these methods there exist different operating procedures. The problem is which is better or more efficient of the two methods in determining the values of variables of the equations simultaneously. This study aimed to compare the solution with the numerical method in determining the approach to the values of variables of equations simultaneously. Based on the average iteration, Newton-Rapshon method had an average recurrence smaller than the average iteration on the method of iteration, so the method of Newton-Rapshon was better or more efficient in solving the approach to the values of variables of simultaneous equations.